Radial Forearm Free Tissue Transfer to Clival Defect - Moy, Jennifer D.; Gardner, Paul A.; Sridharan, Shaum; Wang, Eric W. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Reconstruction of craniocervical junction (CCJ) defects after endoscopic endonasal skull base surgery (ESBS) remains challenging, despite advancements in vascularized intranasal and regional flaps. Microvascular free tissue transfers have revolutionized reconstruction in open skull base surgery but have been utilized rarely in ESBS. We describe the use of a radial forearm free flap (RFFF) for reconstruction of a recalcitrant CCJ defect after resection of a clival chordoma.Case Report A 54-year-old female who underwent ESBS for a clival chordoma complicated by a C1–C2 epidural abscess after proton beam therapy presented with pneumocephalus 4 years after her resection (Fig. 1). At the CCJ, she developed a 1-cm skull-base defect. An occult cerebrospinal fluid (CSF) leak persisted despite an extracranial pericranial flap and a lateral nasal wall flap. Her definite reconstruction was a RFFF inset through a transmaxillary approach. Using a maxillary vestibular incision, anterior, lateral, and medial maxillotomies allowed the introduction of the flap into the nasal cavity and the passage of the RFFF pedicle across the posterior maxillary wall, into the premassateric space and to the facial vessels at the mandible. An endonasal inset supplemented with transoral suturing of the distal end of the flap to the posterior oropharynx halted further CSF egress. Vascularization of the flap was confirmed with intraoperative indocyanine green angiography and postoperative computed tomography (CT) angiography and magnetic resonance imaging (MRI).Conclusion A RFFF inset through a transmaxillary approach to the facial vessels has an adequate reconstructive surface and pedicle to cover the central and posterior fossa skull base after ESBS (Fig. 2).The link to the video can be found at: https://youtu.be/rQ5vJKyD5qg.
Keywords: craniocervical junction; clival chordoma; endoscopic endonasal; radial forearm free flap